The self-selection of commuters - Peter Huber (University of Salzburg, Department of Social Sciences and Economics, 2011)
I analyze the skill structure of commuters in 15 EU countries. Theory suggests that higher returns to education in receiving regions and shorter commuting distances favor positive selection of commuters. Empirically all types of commuters in most EU countries are more skilled than non-commuters. Internal commuters (in particular to capital city regions) are more strongly selected than cross-border commuters, selectivity of commuters reduces with distance commuted and cross-border commuters more often than migrants have an intermediary educational attainment but less often a completed tertiary education.
Keywords: J61; R23; 330; Commuting; Selectivity; Migration